Career planning during the COVID-19 pandemic. Training for strengthening courage and career adaptability and lowering fear levels of COVID-19 - Zammitti, Andrea (Psychology Hub, 2022)
Career development starts from childhood and during adolescence professional planning becomes a very important activity that is influenced by internal and external factors: the COVID-19 pandemic can be one of these factors. To overcome the fear that may arise about the current situation and to be able to plan their future considering recent changes in the world of work, adolescents need positive resources such as courage, defined as the tendency to act despite fear, and career adaptability, the ability to adapt to changes in the world of work. With the aim of lowering the levels fear of COVID-19 and raising the levels of courage and career adaptability, a training was developed that involved 63 adolescents (experimental group); another 62 adolescents (control group) were involved in pre- and post-training measurements. The results showed that the experimental group, after training, had lowered the levels of fear of COVID-19 and raised personal resource levels, while the control group showed higher levels of fear of COVID-19 in the second administration. This means that guidance practices can have an impact on the emotional experience of young people in the period of the pandemic and support them in planning their future.